2008
DOI: 10.1038/onc.2008.457
|View full text |Cite
|
Sign up to set email alerts
|

ATM mediates constitutive NF-κB activation in high-risk myelodysplastic syndrome and acute myeloid leukemia

Abstract: The anti-apoptotic transcription factor nuclear factor-jB (NF-jB) is constitutively activated in CD34 þ myeloblasts from high-risk myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) patients. Inhibition of NF-jB by suppressing the canonical NF-jB activation pathway, for instance by knockdown of the three subunits of the inhibitor of NF-jB (IjB) kinase (IKK) complex (IKK1, IKK2 and NEMO) triggers apoptosis in such cells. Here, we show that an MDS/AML model cell line exhibits a constitutive interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 40 publications
5
44
0
Order By: Relevance
“…They also provide further evidence of an important functional association between HDACI-induced ROS and DNA damage, as well as support for the notion that NF-B activation plays a major role in protecting cells, via Mn-SOD2 induction, from genomic damage and apoptosis (76). The present findings now integrate previous observations implicating HDACI-related ROS generation and DNA damage with emerging evidence linking the prosurvival NF-B pathway to the DNA damage response (20,54). The recent identification of NEMO as an ATM substrate thus provides a connection between HDACI-mediated DNA damage responses and a nuclear-to-cytoplasmic signaling cascade that activates the IKK/NF-B system (20,53).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…They also provide further evidence of an important functional association between HDACI-induced ROS and DNA damage, as well as support for the notion that NF-B activation plays a major role in protecting cells, via Mn-SOD2 induction, from genomic damage and apoptosis (76). The present findings now integrate previous observations implicating HDACI-related ROS generation and DNA damage with emerging evidence linking the prosurvival NF-B pathway to the DNA damage response (20,54). The recent identification of NEMO as an ATM substrate thus provides a connection between HDACI-mediated DNA damage responses and a nuclear-to-cytoplasmic signaling cascade that activates the IKK/NF-B system (20,53).…”
supporting
confidence: 78%
“…DNA damage-mediated NF-B activation is dependent upon interactions between the ATM kinase and IKK␥ (NEMO) (20,54). Phosphorylation of ATM, one of the initial kinases activated in response to DNA damage (55), was monitored in cells exposed to LBH-589.…”
Section: Hdacis Trigger Nf-b Through a Nemo-dependent Process In Assomentioning
confidence: 99%
“…In addition to normal physiological DSBs that can lead to ATM-NEMO-dependent NF-κB activation, a recent study by Grosjean-Raillard et al [75] provides compelling evidence that ATM-NEMO-NF-κB signaling is constitutively activated in certain acute myeloid leukemia (AML) cell lines and more significantly a high percentage of primary myelodysplastic syndrome (MDS) and AML patient samples. Using the P39 AML cell line, the authors showed that ATM is constitutively active, NEMO and PIDD are constitutively nuclear, and an ATM-NEMO nuclear complex is also detectable.…”
Section: Atm-nemo Signaling In Pathologymentioning
confidence: 99%
“…Although the role of nuclear NEMO was originally discovered in the context of genotoxic stress-induced NF-B signaling (14), recent studies have further implicated its potential role in mediating additional processes, including the pathogenesis of myeloid dysplastic syndrome and acute myeloid leukemia (35), resistance to histone deacetylase inhibitors (36), and premature aging syndromes (37,38). Adding to the classical importin ␣-dependent nuclear import pathway mediating the nuclear import of some of the NF-B family members (76 -79), coupled with the recent identification of the Ran-GDP/ankyrin repeat ("RaDAR") import pathway for the IB family of proteins (49), our current identification of the IPO3 nonclassical import pathway in regulation of NEMO nuclear import not only expands our fundamental understanding of the nuclear trafficking aspects of the NF-B signaling system but also points to new therapeutic strategies against cancer resistance as well as the aforementioned medical conditions by targeting the NF-B system-related nuclear import mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Once the IKK complex is active, IB is phosphorylated and degraded to release NF-B to the nucleus via the canonical signaling cascade. Under genotoxic and oxidative stress circumstances, activated IKK and/or NF-B have been shown to modulate apoptosis (16 -18, 23-27), DNA repair (28,29), cell cycle arrest (30,31), and synthesis of inflammatory mediators (32,33), thereby contributing to oncogenesis (34,35), drug resistance (36), and premature aging (37,38).…”
mentioning
confidence: 99%